Effects of green algae and napa cabbage on life-history parameters and gut microflora of Archegozetes longisetosus (Acari: Oribatida) under laboratory conditions - Seniczak, Anna; Ligocka, Anna; Seniczak, Stanisław; Paluszak, Zbigniew (Biological Letters, 2017)
We compared the effect of green algae (dominated by Protococcus sp.) and the earlier studied napa cabbage on the life-history parameters and gut microflora of the oribatid mite Archegozetes longisetosus (a chelicerate model organism). Napa cabbage contained more crude ash, protein, and crude fibre than green algae, but A. longisetosus developed better on the latter food, displaying higher fertility, lower mortality of offspring and shorter development than on napa cabbage. The gut microflora of A. longisetosus depended on the kind of food and developmental stage of this mite. The adults fed with napa cabbage had more abundant and more active microflora than those fed with green algae, whereas in the tritonymphs the microflora was more abundant when they were fed with green algae, and was more active in the group fed with napa cabbage. Irrespective of the treatment, the highest percentage of the isolated bacteria were gram-positive bacilli or gram-negative bacteria, but the mites feeding on Protococcus sp. contained no cocci, whereas those fed with cabbage had no gram-positive bacteria.